Burton's microbiology for the health sciences - Engelkirk, Paul G.; Burton, Gwendolyn R. W. (Gwendolyn R. Wilson; Duben-Engelkirk, Janet L. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"This textbook is designed specifically for students and professionals in the health sciences. As you advance through the text, you'll not only gain a solid foundation in microbiology, you'll also learn to apply you new knowledge to provide patients with safe, effective care." "This Ninth Edition has been thoroughly updated to help you discover how microbes cause disease and how the body protects itself from pathogens and infectious diseases. The text's easy-to-follow explanations will help you to understand common as well as new and emerging microbial threats. Moreover, you'll get the lastest information on such key topics as antibiotics and other antimicrobial agents, epidemiology and public health, healthcare-associated infections, infection control and laboratory tests used to assist in the diagnosis of infectious diseases."--BOOK JACKET
Microbiology : the science -- Viewing the microbial world -- Cell structure and taxonomy -- Microbial diversity -- Microbial diversity -- Biochemistry : the chemistry of life -- Microbial physiology and genetics -- Controlling microbial growth in vitro -- Controlling microbial growth in vivo using antimicrobial agents -- Microbial ecology and microbial biotechnology -- Epidemiology and public health -- Healthcare epidemiology -- Diagnosing infectious diseases -- Pathogenesis of infectious diseases -- Nonspecific host defense mechanisms -- Specific host defense mechanisms : an introduction to immunology -- Overview of infectious diseases -- Viral infections -- Bacterial infections -- Fungal infections -- Parasitic infections
Includes bibliographical references and index
13
Keywords: Allied health personnel; Communicable Diseases -- microbiology; Medical microbiology; Microbiological Processes; Microbiology